2011
DOI: 10.1093/jnci/djr237
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between CYP2A6 and CHRNA5-CHRNA3-CHRNB4 Variation and Smoking Behaviors and Lung Cancer Risk

Abstract: Genetic variations in the CYP2A6 nicotine metabolic gene and the CHRNA5-CHRNA3-CHRNB4 (CHRNA5-A3-B4) nicotinic gene cluster have been independently associated with lung cancer. With genotype data from ever-smokers of European ancestry (417 lung cancer patients and 443 control subjects), we investigated the relative and combined associations of polymorphisms in these two genes with smoking behavior and lung cancer risk. Kruskal-Wallis tests were used to compare smoking variables among the different genotype gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
192
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(214 citation statements)
references
References 25 publications
16
192
4
Order By: Relevance
“…The association of lower FTND scores with lower NMR is consistent with previous reports suggesting that smokers with slower nicotine metabolism may be less-dependent than those with faster metabolism (Mwenifumbo et al, 2007;Rao et al, 2000;Wassenaar et al, 2011). Although other studies did not find an association between NMR and the level of nicotine dependence (Johnstone et al, 2006), smokers with faster nicotine metabolism reported greater craving for cigarettes following overnight abstinence from smoking.…”
Section: Discussionsupporting
confidence: 89%
“…The association of lower FTND scores with lower NMR is consistent with previous reports suggesting that smokers with slower nicotine metabolism may be less-dependent than those with faster metabolism (Mwenifumbo et al, 2007;Rao et al, 2000;Wassenaar et al, 2011). Although other studies did not find an association between NMR and the level of nicotine dependence (Johnstone et al, 2006), smokers with faster nicotine metabolism reported greater craving for cigarettes following overnight abstinence from smoking.…”
Section: Discussionsupporting
confidence: 89%
“…Slow nicotine metabolism, measured by CYP2A6 genotype or NMR, is associated with lower cigarette consumption among dependent adults smoking a mean of 18+ cigarettes/day (Chenoweth et al, 2014;Malaiyandi et al, 2006;Wassenaar et al, 2011). Future investigations will clarify whether dependent adolescent smokers, even at comparatively lower levels of cigarette consumption versus adults, titrate their level of nicotine intake according to their rate of nicotine metabolism in order to maintain desirable levels (Ashton et al, 1979;Hill and Marquardt, 1980), with CYP2A6 slow metabolizers needing to smoke fewer cigarettes to achieve these levels.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2A6 inactivates nicotine, the principle psychoactive compound in cigarette smoke, to cotinine (Nakajima et al, 1996). Genetic variation in CYP2A6 that reduces the rate of nicotine metabolism is associated with lower cigarette consumption (Malaiyandi et al, 2006;Wassenaar et al, 2011), dependence scores Sofuoglu et al, 2012;Wassenaar et al, 2011), brain response to smoking cues (Tang et al, 2012), and greater cessation (Gu et al, 2000;Lerman et al, 2006;Schnoll et al, 2009), even in adolescence (Chenoweth et al, 2013). In adolescents, CYP2A6 slow nicotine metabolism was also associated with an increased risk of tobacco dependence acquisition at young ages (from age 12-16 years) (Al O'Loughlin et al, 2004), but slower escalation in nicotine dependence (Audrain-McGovern et al, 2007) and reduced cigarette consumption (O'Loughlin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of CYP2A6 alleles to genotype depends largely on the allele frequencies within the population under study [4,16,17,26]. For statistical analyses individuals are often separated by genotype into predicted reduced or normal CYP2A6 metabolic activity groups [5,6] with the caveat that activity predictions may be substrate specific. Gene variants affecting the amount of CYP2A6 protein (e.g.…”
Section: Cyp2a6 Genotyping Project Considerationsmentioning
confidence: 99%
“…risk factor for lung cancer among Caucasian, African American and Japanese smokers [5][6][7][8], and CYP2A6 enzymatic activity, which is influenced by genetic polymorphisms, has been investigated as a tool for optimizing the selection of smoking cessation pharmacotherapy [9][10][11].…”
mentioning
confidence: 99%